2019
DOI: 10.1111/gwat.12907
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting “An Exercise in Groundwater Model Calibration and Prediction” After 30 Years: Insights and New Directions

Abstract: In 1988, an important publication moved model calibration and forecasting beyond case studies and theoretical analysis. It reported on a somewhat idyllic graduate student modeling exercise where many of the system properties were known; the primary forecasts of interest were heads in pumping wells after a river was modified. The model was calibrated using manual trial‐and‐error approaches where a model's forecast quality was not related to how well it was calibrated. Here, we investigate whether tools widely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…The robustness of the PEST inversion program has been demonstrated in a number of studies, see, e.g., Anderson et al (2015) and Hunt et al (2019), and is not reassessed here. The purpose of this section is to assess the accuracy of MFIT direct simulations through five synthetic test cases.…”
Section: Code Verificationmentioning
confidence: 78%
“…The robustness of the PEST inversion program has been demonstrated in a number of studies, see, e.g., Anderson et al (2015) and Hunt et al (2019), and is not reassessed here. The purpose of this section is to assess the accuracy of MFIT direct simulations through five synthetic test cases.…”
Section: Code Verificationmentioning
confidence: 78%
“…For example, the authority collected clustered water-level measurements, which could have been optimized if a comprehensive study was conducted before drilling wells. In addition, no base-flow data were collected even though a single base-flow measurement significantly improves uncertainty quantification [36]. This study also demonstrated that if a contaminant reached the upper layer (for example during storm events that raise the water table), it will travel much faster to surrounding streams.…”
Section: Discussionmentioning
confidence: 97%
“…That evaluation of software approaches focused on the Gauss-Levenberg-Marquardt (GLM) approach to deterministic parameter estimation as popularized by the PEST software Doherty (2018). Hunt et al (2020) conclude with a recognition that additional utility of uncertainty for forecasts and repeatability could be gained through scripting. White et al (2020aWhite et al ( , 2020b addressed the inclusion of automated forecast uncertainty analyses needs through additional capabilities in PEST++ version 5 and demonstrated their use on an enhanced "Freyberg model," where the problem was made more complex in space and time.…”
Section: Introductionmentioning
confidence: 98%
“…The classic Freyberg (1988) paper on a classroom exercise in parameter estimation documented insights and shortcomings in a trial-and-error approach during a time that predates widely available software dedicated to parameter estimation and uncertainty analysis. Hunt et al (2020) revisited the classroom exercise from the Freyberg (1988) paper to explore how newer techniques and more modern tools could obviate shortcomings of the results obtained by students in Freyberg (1988) paper. That evaluation of software approaches focused on the Gauss-Levenberg-Marquardt (GLM) approach to deterministic parameter estimation as popularized by the PEST software Doherty (2018).…”
Section: Introductionmentioning
confidence: 99%